2011
DOI: 10.1007/s12975-011-0128-7
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Pathology as a Potential Therapeutic Target in SCI

Abstract: Acute traumatic spinal cord injury (SCI) is characterized by a progressive secondary degeneration which exacerbates the loss of penumbral tissue and neurological function. Here, we first provide an overview of the known pathophysiological mechanisms involving injured microvasculature and molecular regulators that contribute to the loss and dysfunction of existing and new blood vessels. We also highlight the differences between traumatic and ischemic injuries which may yield clues as to the more devastating nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 182 publications
(242 reference statements)
1
11
0
Order By: Relevance
“…Indeed, mechanical injury to the spinal cord rapidly damages the spinal microvasculature resulting in acute intraspinal bleeding with progressive hemorrhagic necrosis (PHN), which is highly destructive. In fact, interventions that prevent or reduce PHN after SCI are markedly protective (Noble and Wrathall, 1989a; 1989b; Hill, 2001; Simard et al, 2007; 2010; Benton and Hagg, 2011; Popovich et al, 2011; Simard et al, 2012; 2013). However, bleeding can have conflicting effects on glia, especially oligodendrocyte lineage cells.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mechanical injury to the spinal cord rapidly damages the spinal microvasculature resulting in acute intraspinal bleeding with progressive hemorrhagic necrosis (PHN), which is highly destructive. In fact, interventions that prevent or reduce PHN after SCI are markedly protective (Noble and Wrathall, 1989a; 1989b; Hill, 2001; Simard et al, 2007; 2010; Benton and Hagg, 2011; Popovich et al, 2011; Simard et al, 2012; 2013). However, bleeding can have conflicting effects on glia, especially oligodendrocyte lineage cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Early vasospasm, including that of the pial vessels, causes ischemia in rats and cats as identified by microangiography and hydrogen clearance measurements. [5][6][7] SCI also results in hemorrhage caused by microvascular disturbances and results in secondary hemorrhagic necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…4 Remodeling of spinal cord vasculature has an important role in the process of repair after SCI. 25 Posttraumatic spinal cord angiogenesis is a local metabolic adaptation to improve spinal cord ischemia. Studies have demonstrated temporary angiogenesis in the damaged and surrounding areas of the central nervous system at 3-7 days after trauma, a peak in angiogenesis at 7 days, and a gradual reduction thereafter.…”
Section: Discussionmentioning
confidence: 99%